“Efecto del cazomet con solarización, como alternativa al bromuro de metilo en el cultivo de tabaco (nicotiana tabacum) Juan Guerra-San Martín” - Oliveira Arévalo, Miguel Angel (2003)
Effect gives the Dazomet with solar radiation, as alternativa to the Bromide gives Methyl in the cultivation he/she gives Tobacco (Nicotiana tabacum) Juan Guerra - San Martín, had as objectives: To evaluate the effect gives the DAZOMET ín combination with solar radiation like alternative method for the disinfecting he/she gives beds almacigueras in the production he/she gives plants he/she gives tobacco and to evaluate the cost of production gives the studied treatments. A totally at random design was used with 2 repetitions and 1 treatments for the analysis nematologico and with 6 treatments for the analysis micologico (Mushrooms) in the laboratory and a DBCA in room for plants with 1 O treatments and 4 repetitions for treatment. lt was studied 1 O treatments with 4 repetitions each a, give which 2 were witness, the treatments were (T1, T2,T3,T4,T5,T6, T7,T8,T10), give 5, 1 O, 15, 20 days with air chamber and 5, 1 O, 15, 20 days without air chamber. The effect gives control to 100% he/she gives nematode for the population and goods found in the samples give floor (Pratylenchus sp., Paratylenchus sp., Thylenchus sp. ), one observes from a treatment he/she gives the substrates with Dazomet with 5 days he/she gives action he/she gives the same one. The control gives mushrooms fitopatógenos (Pythium sp., Phytophthora sp., Fusarium sp.) found in the sample he/she gives floor and treaties with Dazomet to a dose he/she gives 40 gr. for square meter he/she gives substratum and with 15 to 20 days gives action they threw the best results he/she gives control with 100% and 81 % with air chamber and from 86% up to 100% without air chamber respectively, comparable to the treatment with Bromide gives methyl. The effect gives control he/she gives overgrowths he/she g.ives wide leaf (AIDS sp., Portulaca sp.) and it narrows (Cyperus sp., Rotboelía sp.), they overcame statistically the witness without treatment with 35, 1 %, 48.81 %, 51.67%; 58,9% and 97, 1 % for 20, 15, 1 O, 5 days he/she gives treatment with Dazomet and for the Witness tried respectively with BM. The use gives the Dazomet to a dose he/she gives 40 g. for square meter it is constituted asan economic alternativa method, technical and ecologically viable to the use he/she gives the Bromide he/she gives methyl in the disinfecting he/she gives substrates for the production he/she gives plants he/she gives tobacco.